Chapter 5 - Application of Biosurfactants for Microbial Enhanced Oil Recovery (MEOR) - Correia, Jéssica (2021)
Despite the significant efforts to expand the use of renewable energy sources, our society is still highly dependent on crude oil. The progressive exhaustion of light crude oil reserves forced the oil companies to develop alternative strategies to recover the entrapped oil remaining in the reservoirs. These technologies, known as Enhanced Oil Recovery, use chemical compounds to increase oil production. One of the most important strategies is the injection of surfactants into the oil wells to reduce the high capillary forces that entrap the oil into the rock pores. Biosurfactants, surfaceactive compounds synthesized by microorganisms, are a promising alternative to the chemical surfactants for application in oil recovery. Biosurfactants usually exhibit excellent surface activity and are stable at extreme conditions, are environmentally friendly, and can be produced using agroindustrial byproducts. This chapter will review the latest advances on the application of biosurfactants in Microbial Enhanced Oil Recovery.